Konstitusionalitas Pelunasan Utang Pajak Perusahaan Pailit Berdasarkan Putusan Pengadilan - Bagus Surya Prabowo; Wiryanto Wiryanto (The Constitutional Court of the Republic of Indonesia, 2021)
The decision of the Constitutional Court Number 41/PUU-XVIII/2020 states that the appointment of the management as a representative of a taxpayer in the form of an entity aims to guarantee certainty that the actions of a legal entity can be held accountable, equivalent to the guarantee of the right of a legal entity to do or not to do something for the sake of the legal entity in question (which incidentally ends up in the interests of the management and shareholders). The management is the main party who is held accountable for the actions/actions of a legal entity because the management operates it in a daily basis. The imposition of responsibilities of a legal entity (which cannot do anything without human assistance) to a person or group of management is not contrary to the 1945 Constitution. Likewise in the case of corporate tax obligations, the provisions that impose the settlement of an entity's tax obligations (debts) bankrupt company tax) to the management of the agency represented by the curator is in accordance with the 1945 Constitution. In accordance to Article 32 paragraph (2) of the KUP Law with the norms of the 1945 Constitution, especially in terms of providing protection and fair legal certainty to all parties interacting with legal entities, including the Applicant who is the administrator of the legal entity, as guaranteed by Article 28D paragraph (1) of the 1945 Constitution. One form of the rights of the parties that interacts with legal entities is the right of the state to receive payment of taxes from a certain legal entity through a party or person acting as the administrator of the legal entity. This article discusses the constitutionality of paying tax debts to companies that declared bankrupt by a court decision.